Evaluation of pulsed electromagnetic field therapy to improve muscle strength and functional aspects in the elderly: A pilot study - Leonardo , Patrícia Sardinha; Cardoso, Katiele Rodrigues da Silva; Oliveira Silva, Bruno; Silva, Ruan Oliveira; Silva, Helen Cristina de Araújo; França, Paulo Ricardo Pinheiro; Souza, Beatriz Nascimento; Moreira, Isabella Layne Teodoro; Coelho, Carly de Faria; Oliveira, Cláudia Santos; Filho, Alberto Souza de Sá; Lopes-Martins, Rodrigo Alvaro Brandão (Manual Therapy, Posturology & Rehabilitation Journal, 2023)
Backgroung: Sarcopenia has been defined as a progressive and generalized disorder of skeletal muscle that involves accelerated loss of muscle mass and function. The prevalence of sarcopenia worldwide is up to 15% in healthy elderly, approximately 76% of acutely hospitalized elderly patients, and up to 69% of patients admitted for post-acute geriatric rehabilitation. The loss of muscle mass results in serious consequences and several chronic diseases and senility, characterized by functional losses, muscle weakness, loss of independence and increased risk of falls and death. Sarcopenia has been defined as a progressive and generalized muscle disorder. Here we investigate the effects of PEMF in muscle strength and functional capabilities of elderly sarcopenic patients. Methods. Fifteen elderly people of both sexes, aged between 65 and 80 years old, classified according to the degree of muscle weakness. The participants were submitted to PEMF therapy in 12 sessions three times a week with the following parameters. In the first two sessions, only submaximal contraction was applied during 30 min with a frequency of 5 Hz at the sport mode of the equipment. In the following 10 sessions we used cycles of Submaximal contractions – frequency of 5 Hz with 5s duration and Supramaximal contractions – frequency of 30 Hz with 5s duration. The intensity of the equipment was adjusted according to the sensitivity of the patient and session duration was 30 min. Results. the TUG functional tests showed a significant reduction in execution time, with an initial average of 40 ± 10s to 22 ± 6s after treatment sessions. The average increase in muscle strength was 27 ± 9% after PEMF treatment. Conclusions. This case series report is the first in the world scientific literature to demonstrate the effectiveness of PEMF (Supramaximus™) therapy in gaining muscle strength and functionality in elderly sarcopenic patients. PEMF therapy, at least for the treatment of sarcopenia in the elderly, can be considered as the definitive evolution of electrical currents, with greater effectiveness and acceptance by the patient.